Application of high flux brackish water thin film composite membranes in the desalination of highly saline ground water. (7th May 2007) - Joshi, S.V.; Devmurari, C.V.; Trivedi, J.J.; Prakash Rao, A.; Shah, V.J.; Ghosh, P.K.
The improvements in flux and membrane designs have enabled us to install smaller and economical two-stage reverse osmosis systems suitable for small village communities situated near coastal areas to provide safe drinking water. In addition, the advent of higher productivity and better salt rejection membranes has allowed us to operate the systems at low pressure in both stages. Our two-stage sequential reverse osmosis system has been field tested, and proved economically feasible. The product water quality obtained from this system is 500 ppm to 700 ppm from highly saline (equivalent to seawater, 35, 000 ppm) water. The two-stage reverse osmosis design permits the system to operate for much longer periods using the same membrane modules and to produce better-quality product water. Reported herein are the results of the application of the high-flux thin-film composite membrane in a two-stage desalination plant to treat highly saline groundwater at village Nelmadur in Ramnathpuram district in Tamil Nadu.